MANAJEMEN SEKOLAH DASAR DALAM MENANGANI SISWA DI LINGKUNGAN MARGINAL - Yudi Permana; Jhoni Martin FR; Hosiana Wirastri; Yulia Efendi; Rahman Rosyadi; Dinny Mardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze elementary school management in handling students from marginalized social environments at Kanoman Elementary School. The background of the study is based on the socioeconomic conditions of the community surrounding the school, which is vulnerable to problems of poverty, domestic violence, crime, and low parental education, which impact student learning motivation, behavior, and discipline. This study used a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation studies. Informants consisted of the principal, teachers, school committee members, and parents. The results show that school management is implemented through four main functions: (1) Planning, by developing a program for handling problem students based on empathy and social needs; (2) Organizing, through the formation of a Problem Student Handling Team (TPSB) involving teachers and the school committee; (3) Actuating, through implementing interventions such as home visits, character development, simple counseling services, motivational classes, and collaboration with village officials; and (4) Controlling, through routine evaluations, monitoring student behavior, and the application of non-violent discipline. This study concludes that a humanistic, collaborative, and character-focused management approach can create a safer, more inclusive learning environment that supports the development of students from marginalized families. These findings can serve as a reference for other schools in developing strategies for managing students with social problems.